A case of selpercatinib treatment for anaplastic thyroid carcinoma resulting in abscess formation - Kuboki, Ryo; Nomura, Fuminori; Yagihashi, Satoshi; Asakage, Takahiro (International cancer conference journal, 2024)
Rearranged during transfection ( RET ) gene abnormality is a driver gene mutation that causes thyroid cancer, and selpercatinib has been shown to be useful for treating thyroid cancer with RET gene abnormalities. Anaplastic thyroid cancer is a disease with an extremely poor prognosis with no standard treatment established, and there are only one case reports of the efficacy of selpercatinib for RET fusion gene-positive anaplastic thyroid cancer. We herein report our experience treating an old Japanese woman with unresectable anaplastic thyroid cancer with selpercatinib. Surgical resection was initially attempted but was not possible due to adhesion to the common carotid artery. Postoperative genetic testing was positive for the RET fusion gene, and selpercatinib was administered. However, the administration had to be stopped due to the formation of an abscess on day 14 and a pharyngeal fistula on day 17, after which the tumor grew rapidly, and the patient died on day 65. Although selpercatinib has been reported to have a high safety profile with few adverse events, this case suggests that caution should be exercised when treating anaplastic thyroid cancer with invasion to vital organs.